Psychological Well-Being During the Great Recession: Changes in Mental Health Care Utilization in an Occupational Cohort. - Modrek, Sepideh; Hamad, Rita; Cullen, Mark R. (American Journal of Public Health, 2015)
Objectives. We examined the mental health effects of the Great Recession of 2008 to 2009 on workers who remained continuously employed and insured. Methods. We examined utilization trends for mental health services and medications during 2007 to 2012 among a panel of workers in the 25 largest plants, located in 15 states, of a US manufacturing firm. We used piecewise regression to compare trends from 2007 to 2010 in service and medication use before and after 2009, the year of mass layoffs at the firm and the peak of the recession. Our models accounted for changes in county-level unemployment rates and individual-level fixed effects. Results. Mental health inpatient and outpatient visits and the yearly supply of mental health–related medications increased among all workers after 2009. The magnitude of the increase in medication usage was higher for workers at plants with more layoffs. Conclusions. The negative effects of the recession on mental health extend to employed individuals, a group considered at lower risk of psychological distress.